Exploring the impact of green investment on quality of life: comparative study of China and Belarus from the perspective of economic growth - Shao, Ziyu; Dzeraviaha, Ihar P.; Ning, Jing (Journal of the Belarusian State University. Economics, 2024)
The impact of green investment on quality of life from the perspective of economic growth is investigated. Panel data and fixed effects models for 30 provinces in China as well as 6 regions and the capital city of Belarus for the period from 2010 to 2020 are used to study this process. The results show that holding other conditions constant, a 1.0 % increase in green investment can accelerate economic growth by 0.22 %. A comparative analysis of the impact of green investment on economic growth in China and Belarus is carried out. Significant differences in their impact are identified. It is argued that the economic benefits of green investment in Belarus are about three times higher than in China. These findings remain valid if the endogeneity problem is taken into account and a series of robustness checks are conducted. Appropriate economic policy measures are proposed to improve the quality of life and increase the economic benefits of green investment.
Keywords: green investment; quality of life; economic growth; China; Belarus